1993
DOI: 10.1080/03057269308560019
|View full text |Cite
|
Sign up to set email alerts
|

Situated Cognition and Cognitive Apprenticeship: Implications for Classroom Learning

Abstract: INTRODUCTIONThis paper reviews recent research in the area of situated cognition, focusing on the domains of mathematics, science and technology. The key issue addressed here is the disjunction between classroom learning and cognition in practice. The notion of apprenticeship inside and outside the classroom, the potential scaffolding function of computer-based learning environments, the role of prior knowledge in learning, and the notion of a general thinking and problem-solving capability are also explored, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
0
9

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(119 citation statements)
references
References 59 publications
(47 reference statements)
2
108
0
9
Order By: Relevance
“…The realisation that there are people out in the real world who actually require aids to help them do everyday tasks and that aids are actually made for these people had an impact on the solutions offered by the children. By making use of a deliberate social context (Hennessy, 1993) the activity became more relevant and meaningful as the children realised that anyone could become one-handed at any time and that people do actually design aids to help one-handed people. This highlights the need for recognition that technology is socially constructed and has huge consequences for quality of life for some people.…”
Section: Resultsmentioning
confidence: 99%
“…The realisation that there are people out in the real world who actually require aids to help them do everyday tasks and that aids are actually made for these people had an impact on the solutions offered by the children. By making use of a deliberate social context (Hennessy, 1993) the activity became more relevant and meaningful as the children realised that anyone could become one-handed at any time and that people do actually design aids to help one-handed people. This highlights the need for recognition that technology is socially constructed and has huge consequences for quality of life for some people.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, time for teachers to engage in intellectual and professional conversation needs to be in-built, to create a mutually respectful, inquiring community. Underpinning ideas centre on learning as a situated-social knowledge construction process and an active process empowered via collaborative activity (Hennessy, 1993;Lave & Wenger, 1991).…”
Section: Classroom Researchmentioning
confidence: 99%
“…However, it also refers to the use of current issue examples or real life situations which they familiarize themselves and creates a learning environment where students require knowledge (Ayvacı et al, 2013). The studies conducted have revealed that CBL approach is quite effective for students to understand chemistry concepts better and to improve positive attitudes towards chemistry (Bennett and Lubben, 2006;Bulte, Klaassen, Westbroek, Stolk, Prins, Genseberger, de Jong and Pilot, 2006;Dlamini and Lubben, 1996;Hennessy, 1993;Murphy, 1994;Ramsden, 1992;Sözbilir et al, 2007). Moreover, there are also findings which reveal that CBL promotes student motivation towards chemistry and it enables students to associate abstract subjects or concepts with the daily life situations and thus facilitates learning.…”
Section: Extended Abstract Introductionmentioning
confidence: 99%
“…BTÖ yaklaşımı ilk olarak 1980'li yılların başında İngiltere'de York Üniversitesinde bir grup kimya eğitimcisi tarafından önerilmiştir (Ayvacı, Ültay ve Mert, 2013 (Demircioğlu, 2008). BTÖ yaklaşımının temel amacı, öğrenilecek kavramları günlük yaşamdan seçilmiş olaylar ile ilişkilendirerek (Ayvacı ve ark., 2013) öğrencilerin motivasyon ve derse karşı isteklerini artırmak (Bennett ve Lubben, 2006;Bulte, Klaassen, Westbroek, Stolk, Prins, Genseberger, de Jong ve Pilot, 2006;Dlamini ve Lubben, 1996;Hennessy, 1993;Murphy, 1994;Ramsden, 1992), fene karşı ilgilerini çekmek (Akpınar, 2009;Graber, Erdmann ve Schlieker, 2002;Hofstein ve Kesner, 2006;Kutu ve Sözbilir, 2011;King ve Ritchie, 2007;Sözbilir, Sadi, Kutu ve Yıldırım, 2007), günlük yaşam olayları ile fen bilimleri arasındaki ilişkinin farkına varmalarını sağlamak ve öğrencilerin bilimsel süreç becerilerini geliştirmektir (Barker ve Millar, 1999Demircioğlu, Dinç ve Çalık, 2013;Sözbilir ve ark., 2007;Potter ve Overton, 2006). BTÖ yaklaşımının uygulama stratejilerinden birisi olan REACT stratejisi Relating (ilişkilendirme), Experiencing (tecrübe etme), Applying (uygulama), Cooperating (iş birliği) ve Transferring (transfer etme) gibi beş temel ilkeden oluşan bir öğrenme stratejisidir.…”
Section: Introductionunclassified
See 1 more Smart Citation